Structural and rheological characterization of pectin from passion fruit (Passiflora edulis f. flavicarpa) peel extracted by high-speed shearing. (May 2021) - Lin, Yupeng; An, Fengping; He, Hong; Geng, Fang; Song, Hongbo; Huang, Qun
Abstract: In this study, the structural and rheological properties of pectin extracted by high-speed shearing (HSS–P) at 50 °C ultrapure water and conventional heating methods (CE50-P and CE90-P) from passion fruit ( Passiflora edulis f. flavicarpa ) peel were evaluated and compared. The HSS-P has loose, honeycomb-like surface morphology, lower molecular weight and higher polydispersity index compared to CE50-P and CE90-P. Monosaccharide composition indicated that HSS-P had more side chains, which were caused by its highly branched molecular structure, short main chains and a high molar ratio of RG-I in the molecular configuration. FTIR spectra showed that high-speed shearing led to a decrease in the linearity of the main chain of the pectin molecule. NMR spectra indicated that the molecular structure of HSS-P was a linear chain of homogalacturonan (HG) inserted into rhamnogalacturonan I (RG-I) possibly with arabinans and galactans as the principal side chains. Furthermore, the effects of pectin concentration, sucrose, CaCl2 and pH on the rheological properties of different pectins were investigated. All pectin exhibited pseudoplastic fluid behavior at different environmental conditions. The HSS-P samples showed the greatest increase in the apparent viscosity and viscoelasticity in the presence of sucrose (60%–100%) and CaCl2 (0.1–0.2 g/100 mL), pH changes and increased pectin concentration. The HSS-P was easily combined with the co-solutes and its viscoelasticity showed stronger stability under temperature changes. In conclusion, the high-speed shearing results in a unique molecular structure that contributed to the excellent rheological properties of pectin. Thus providing theoretical guidance for further application of high-speed shearing in extracting pectin. Graphical abstract: Image 1 Highlights: Pectin from passion fruit peel extracted by high-speed shearing has good rheology. The HSS-P can bind tightly with sucrose and Ca 2+ in the solution. The molecular structure of pectin was altered by high-speed shearing. Pectin's rheological was related to degree of branching and RG-I regions content.